Kelong in the context of the gandrang bulo dance in Makassar - Ade Kurniawan Suhardi; Bambang Sunarto (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
Kelong is a Makassar term meaning 'song,' which is one of the main elements in the Gandrang Bulo dance. Kelong, in this case, is presented simultaneously with elements of Pakakkala' (funny) dance and satirical drama or acting. Kelong is meant to educate, while pakakkala' and satire are humorous to entertain. So far, most appreciators are more interested in entertaining humor than curiosity about the meaning of kelong. This paper aims to reveal the description of the portion of the presentation of kelong in the phenomenon of the Gandrang Bulo dance. This article also tries to articulate the meaning of education and motivation to raise awareness that teaches that life is not in vain. Using a descriptive qualitative methodology, this study. Textual and musical data were specially extracted from poetry using the kelong method, including audio and visual perception. One of the achievements of this research is to provide information that there is an educational meaning tucked into the kelong. The research implementation used a descriptive qualitative method by prioritizing the collection of music data and verbal data as the unit of analysis. The finding of this research is to get the educational value tucked inside the kelong behind disproportionately contrasting elements. The significance of this research is that it really contributes as a driving force for the enthusiasm of artists in educating through the arts, especially kelong.